Platform governance and civil society organisations: Tensions between reform and revolution continuum - Eugenia Siapera; Elizabeth Farries (Internet Policy Review, 2025)
Focusing on the European context and the Digital Services Act, this article probes the role of civil society organisations (CSOs) in platform governance. Theoretically, we locate CSOs within the paradigm of neoliberal governance, which aims to limit state power advancing a market-based rationality. Civil society is tasked with pushing against both state and markets, although in doing so it may end up upholding the terms of neoliberal governance. In this context, we ask, to what extent can digital rights CSOs fulfil their normative role and how do they participate in platform governance? Empirically, we rely on a set of in depth interviews with key informants from five leading EU digital rights CSOs, supported by autoethnography and document analysis. Our findings suggest that CSOs operate across what we refer as the 'reform versus revolution' continuum. While those closer to the 'reform' end aim to make incremental changes to improve platforms, those closer to the 'revolution' end take a more radical view aiming to dissolve platforms altogether. While this structuring division reflects positions that are critical in different ways, pragmatic issues around (i) values, principles and organisational aspects; (ii) financial dynamics including funding and sustainability; and (iii) CSO stakeholder relations with platforms, policy makers, and other CSOs, undermine CSOs' ability to act effectively, let alone engage in a radical repositioning of platform governance terms and impacts.
Keywords: 300; Platform governance; Civil society organisations; Digital Services Act; Digital rights